General vaccination willingness and current vaccination status in relation to clinical and psychological variables in patients with multiple sclerosis. Issue 23 (20th May 2022) - Streckenbach, Barbara; Baldt, Julia; Heidler, Felicita; Frahm, Niklas; Langhorst, Silvan Elias; Mashhadiakbar, Pegah; Burian, Katja; Zettl, Uwe Klaus; Richter, Jörg
Highlights: General vaccination willingness (MS patients) was not related to anxiety/depression. MMR vaccination completeness correlates with younger age in MS patients. Influenza vaccination completeness correlates with higher age in MS patients. Influenza vaccination completeness was related to personality scores and anxiety. Tetanus vaccination completeness was not associated with age or personality scores. Abstract: Background: Infections can have a significant impact on morbidity and mortality in multiple sclerosis (MS) patients. Therefore, vaccinations are of immense importance. If vaccination willingness is to be increased, possible influencing factors should be identified. The aim of the present study was to investigate the status of active immunisation in MS patients in association with sociodemographic, clinical-neurological, psychopathological and personality variables using the NEO-Five Factor Inventory, the Temperament and Character Inventory-Revised and the Hospital Anxiety and Depression Scale. Method: Four hundred and four MS patients from two German neurological hospitals were examined for their vaccination attitudes, in detail, the general willingness to vaccinate and the current vaccination status of mumps, measles and rubella (MMR) as well as tetanus and influenza. We also looked at the current level of disability in relation to the current vaccination status, as well as possible associated personality and psychopathological variables. Results: Patients with a complete MMR vaccination status were significantly younger and those with a complete influenza vaccination status were significantly older than those with related incomplete vaccination status. Tetanus vaccination status completeness did not differ depending on age and did not show substantial association with personality scores. However, influenza vaccination completeness was associated with differences in personality and psychopathological variables; extraversion, openness, novelty seeking, harm avoidance and anxiety. A reported general vaccination willingness was significantly correlated with the current completeness of tetanus and influenza vaccinations. Novelty seeking, persistence, extraversion, agreeableness, conscientiousness and neuroticism were found associated with an increased vaccination willingness. Anxiety and depression were not related to general vaccination willingness. Conclusions: No specific personality trait could be defined on its own in relation to general vaccination willingness or complete vaccination status. Younger patients should be made more aware of influenza vaccination. Reasons for rather low vaccination rates need to be further investigated.